2012
DOI: 10.1111/j.1742-4658.2012.08570.x
|View full text |Cite
|
Sign up to set email alerts
|

Substrate variations that affect the nucleic acid clamp activity of reverse transcriptases

Abstract: We have recently shown that reverse transcriptases (RTs) perform template switches when there is a very short (two-nucleotide) complementarity between the 3¢ ends of the primer (donor) strand and the DNA or RNA template acceptor strands ) Nucleic Acids Res 39, 1042-1053. These dinucleotide pairs are stabilized by RTs that are capable of 'clamping' together the otherwise unstable duplexes. This RT-driven stabilization of the micro-homology sequence promotes efficient DNA synthesis. In the present study, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Biochemical studies showed that a related activity of HIV-1 RT (referred to as "clamping") requires at least 2 bps between the 3Ј end of the cDNA and the acceptor template, one of which must be a GC or CG bp (17). Other retroviral and LTR retroelement RTs also required 2 bps for maximal clamping activity, but in some cases they showed weak activity (24 -36%) with a single bp (18).…”
mentioning
confidence: 99%
“…Biochemical studies showed that a related activity of HIV-1 RT (referred to as "clamping") requires at least 2 bps between the 3Ј end of the cDNA and the acceptor template, one of which must be a GC or CG bp (17). Other retroviral and LTR retroelement RTs also required 2 bps for maximal clamping activity, but in some cases they showed weak activity (24 -36%) with a single bp (18).…”
mentioning
confidence: 99%
“…5), increasing the time window for sampling potential acceptor templates for complementarity. Longer base-pairing interactions assist template switching by retroviral and LTR-retrotransposon RTs (18), but the opposite is true for GsI-IIC RT, with overhang lengths beyond 1-nt decreasing the efficiency of template switching ( Fig. 6 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Template switching by a retroviral RT is also employed for RNA-seq adapter addition in a method called SMART-Seq (Switching Mechanism At the 5' end of the RNA Transcript sequencing), which utilizes the ability of Moloney murine leukemia virus RT to add nontemplated C residues to the 3' end of a completed cDNA, which can then base pair and enable template switching to the 3' end of an adapter DNA oligonucleotide ending with G residues (4,7,16). Biochemical studies showed that efficient template switching by HIV-1 RT requires at least two base pairs between the 3' end of the cDNA and the acceptor template, one of which must be a GC or CG base pair (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…New in vitro evidence, presented recently by us, show that RTs can perform also template switches with even a very short (1 to 2 nt) complementarity between the 3= ends of the primer donor strand and the DNA or RNA template acceptor strands (6)(7)(8). These tiny duplexes are markedly stabilized thermodynamically by the RT that "clamps" together the duplex structures that are otherwise very unstable.…”
mentioning
confidence: 99%
“…This new clamp function is performed, though to variable extents, by all RTs tested but not by cellular DNA polymerases, suggesting that it is potentially essential to retroviral RTN (6). Interestingly, RTs, other than those of HIV and MLV, can also form a stable clamp with even a single nucleotide complementarity between the donor and acceptor strands, and these RTs can tolerate even short 1-to 2-nt gaps between the functional template and the adjacent strand (7).…”
mentioning
confidence: 99%